Can Dunite Promote Physiological Changes, Magnesium Nutrition and Increased Corn Grain Yield? - Crusciol, C. A.C. [UNESP]; Moretti, L. G. [UNESP]; Bossolani, J. W. [UNESP]; Moreira, A.; Micheri, P. H. [UNESP]; Rossi, R. [UNESP] (Taylor & Francis, 2019)
Several efforts have been made in recent years to mitigate the different environmental impacts related to agricultural activities. Rock dust technology is an important soil remineralization mechanism for sustainable tropical agriculture. The objective of this study was to evaluate the effect of dunite rates on magnesium (Mg), silicium (Si), reducing sugars, sucrose and foliar starch, soil chemical attributes and corn yield [Zea mays L.] in two soil types. The treatments consisted of five dunite rates (0, 42, 208, 542, and 1542 mg kg−1) in a clayey soil and five dunite rates (0, 150, 238, 411, and 933 mg kg−1) in a sandy soil. In both crops and soils, the content of Mg, Si, leaf reducing sugars, pH, Mg and Si of the soil and productivity components presented a positive response as a function of an increase in the input dose. However, the higher Mg nutrition resulted in lower levels of sucrose and foliar starch. The better plant partitioning of metabolites led to better development, filling and yield of corn grains.
Keywords: magnesium fertilization; natural soil fertilizers; silicium; volcanic rock powders; Zea mays